Human capital : a critique - Jamil, Rossilah (2004)
Human Capital Theory argues that a person's formal education determines his or her earning power. This article seeks to highlight the discrepancies surrounding the notion that education should be construed as a direct form of investment in one's financial future. An analysis of the use of quantitative techniques in measuring human capital, particularly the full / elaborate and the regression methods is presented. The ways in which returns are measured by using the full / elaborate method and regression method are explained and a critical assessment of their applications is discussed. There are several reasons to dispute the notion that one's education influences earnings. The first is that non-educational factors also influence earnings. Secondly, there are weaknesses in the way 'benefits' and 'costs' of education in Human Capital research are defined. Thirdly, there is skepticism of the indicators of social benefits claimed to have resulted from investment in education. Fourthly, limitations of data sources generally used in Human Capital research tend to distort reality. And finally, weaknesses are inherent in the way that Human Capital research is conducted due to its nature as an economic research